Elska - Hapka, Cathy (Horse diaries, 2009)
Around the year 1000, the Icelandic horse named Elska is born and learns about life and her role in the herd, as well as love and friendship, when she rescues the girl to whom she originally belonged. Includes facts about Icelandic horses and Iceland.